2013
DOI: 10.1177/019874291303900102
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Strategy Development: Connecting Persuasive Writing to Self-Advocacy for Students with Emotional and Behavioral Disorders

Abstract: Students with emotional and behavioral disorders often experience difficulties in expressive writing and social outcomes in school and beyond. Therefore, writing instruction and self-determination skills are critical for this population. This research study, in which special education teachers were trained to be implementers, successfully intertwined persuasive writing with self-determination instruction to improve students' writing and self-determination skills. Emphasis was given to teaching students how per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 15 publications
1
43
0
1
Order By: Relevance
“…The peer-led writing intervention was implemented across 4 weeks and consisted of guided meditation, video prompting, and responsive writing (DeMarco & Chan, 2013). Both writing interventions were found to improve self-advocacy skills (Cuenca-Carlino & Mustian, 2013; DeMarco & Chan, 2013); however, effects were not maintained for the HIV/AIDS writing intervention (DeMarco & Chan, 2013). Writing interventions appear to offer a means for creative expression to promote self-advocacy.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The peer-led writing intervention was implemented across 4 weeks and consisted of guided meditation, video prompting, and responsive writing (DeMarco & Chan, 2013). Both writing interventions were found to improve self-advocacy skills (Cuenca-Carlino & Mustian, 2013; DeMarco & Chan, 2013); however, effects were not maintained for the HIV/AIDS writing intervention (DeMarco & Chan, 2013). Writing interventions appear to offer a means for creative expression to promote self-advocacy.…”
Section: Resultsmentioning
confidence: 92%
“…Two studies analyzed the effects of writing interventions on self-advocacy. One study found positive effects following an intervention in which students with emotional and behavioral disorders learned to write persuasive essays on self-advocacy topics (Cuenca-Carlino & Mustian, 2013). DeMarco and Chan (2013) analyzed the effects of a writing intervention when compared with the “gold standard” of peer-led group interventions for individuals with HIV/AIDS education, support, and self-advocacy promotion (DeMarco & Chan, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants across studies included children and adolescents ranging from 5 (Palmer & Wehmeyer, 2003) to 21 years (Agran & Wehmeyer, 2000). While most studies reported age ranges, means, and standard deviations, only seven studies (20.6%) reported individual grade levels (e.g., Cuenca-Carlino & Mustian, 2013). Most studies were conducted with students exclusively in high school ( n = 8 articles; 23.5%; e.g., Shogren et al, 2012) or a combination of students in high school and 18-21 school-affiliated programs ( n = 10 articles; 29.4%; e.g., Taylor-Ritzler et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Taking PBPD one step further, Cuenca-Carlino et al (2018) demonstrated that a bilingual special education teacher was able to implement SRSD persuasive writing instruction with fidelity in a study where results also showed gains in the writing quality and quantity for nine ELLs in Grades 2 and 3 (including four ELLs with disabilities). Beyond this initial evidence, the availability of practitioner-friendly literature (e.g., Cuenca-Carlino et al, 2016; Cuenca-Carlino & Mustian, 2013) and the accessibility of web-based resources (e.g., “ThinkSRSD”) further corroborate the ease with which special education teachers can learn about how to effectively implement SRSD writing instruction.…”
Section: Self-regulated Strategy Developmentmentioning
confidence: 89%